Pengaruh Ekspektasi Return dan Literasi Keuangan Terhadap Minat Berinvestasi Emas pada Mahasiswa STIE Widya Wiwaha - valen pana; Lilik Ambarwati (Jurnal Akuntansi dan Keuangan, 2023)
The purpose of this study is to examine the effect of return expectations and financial literacy on the interest in investing in gold among students at STIE Widya Wiwaha. The sampling technique used in this study was reference sampling basen on the slovin formula, with a sample size of 91 students from STIE Widya Wiwaha. The research approach used in this study was quantitative.The results of the study indicate that return expectations have a significant effect on the interest of students from STIE Widya Wiwaha, Yogyakarta, in investing in gold bullion, and financial literacy also has a significant effect on their interest in investing in gold bullion. Additionally, return expectations and financial literacy together have a significant effect on the interest of students from STIE Widya Wiwaha, Yogyakarta, in investing in gold bullion.